Rehabilitation of Avulsed Teeth in Fractured Jaws via Bone Grafting and Implant Placement: Report of Two Cases - Anshul Jain; Shridhar Baliga (Tehran University of Medical Sciences, 2016)
The maxillofacial region is one of the most injury-prone areas during road traffic accidents, personal violence, falls and sports. Maxillofacial trauma can lead to breakage or avulsion of upper anterior teeth, which may cause significant aesthetic and functional problems. There are many treatment options available for rehabilitation including removable partial dentures, fixed partial dentures, crown and bridges and implant-supported prostheses. Herein, two cases are presented where implant placement was done for upper anterior teeth, which were traumatized or avulsed following maxillofacial trauma. Both patients demonstrated a history of maxillofacial trauma and had undergone open reduction and internal fixation. The first patient had a severe maxillary alveolar defect treated via autogenous bone grafting and a six-month period was given for proper integration of the bone graft. The second patient was a smoker with very poor oral hygiene and a deep bite. Thus, implant placement was not initially justified.